Thermoneutral housing promotes hepatic steatosis in standard diet-fed C57BL/6N mice, with a less pronounced effect on NAFLD progression upon high-fat feeding - Horakova, Olga; Sistilli, Gabriella; Kalendova, Veronika; Bardova, Kristina; Mitrovic, Marko; Cajka, Tomas; Irodenko, Ilaria; Janovska, Petra; Lackner, Karoline; Kopecky, Jan; Rossmeisl, Martin (Frontiers in Endocrinology, 2023)
Non-alcoholic fatty liver disease (NAFLD) can progress to more severe stages, such as steatohepatitis and fibrosis. Thermoneutral housing together with high-fat diet promoted NAFLD progression in C57BL/6J mice. Due to possible differences in steatohepatitis development between different C57BL/6 substrains, we examined how thermoneutrality affects NAFLD progression in the C57BL/6N mouse substrain. Male mice were fed standard or high-fat diet for 24 weeks and housed under standard (22°C) or thermoneutral (30°C) conditions. High-fat feeding promoted weight gain and hepatic steatosis, but the effect of thermoneutral environment was not evident. Liver expression of inflammatory markers was increased, with a modest and inconsistent effect of TN; however, histological scores of inflammation and fibrosis were generally low (<1.0), regardless of ambient temperature. In standard diet-fed mice, thermoneutrality increased weight gain, adiposity, and hepatic steatosis, accompanied by elevated de novo lipogenesis and changes in liver metabolome characterized by complex decreases in phospholipids and metabolites involved in urea cycle and oxidative stress defense. Thus, thermoneutrality appears to promote NAFLD-associated phenotypes depending on C57BL/6 substrain and/or amount of dietary fat.